Treatment with a combination of bosentan and sildenafil allows for successful liver transplantation in a patient with portopulmonary hypertension - Sağ, Saim; Yeşilbursa, Dilek; Güllülü, Sümeyye (Turkish Journal of Gastroenterology, 2014)
Abstract Pulmonary arterial hypertension (PAH) that occurs in the setting of cirrhosis and portal hypertension is referred to as portopulmonary hypertension (PPHTN). Liver transplantation (LTx) is curative, but the presence of moderate-tosevere PPHTN may be a contraindication for transplantation because of the elevated risk of peri- and post transplantation morbidity and mortality. We report a successful liver transplantation in a patient with liver cirrhosis after treatment of moderate-to-severe PPHTN with a combination of the dual endothelin receptor antagonist bosentan and the specific phosphodiesterase-5 inhibitor sildenafil.